Mass‐Production of Electrospun Carbon Nanofiber Containing SiOx for Lithium‐Ion Batteries with Enhanced Capacity. Issue 3 (7th January 2019) - Moon, Seongjun; Yun, Jisu; Lee, Jae Young; Park, Gyori; Kim, Sung‐Soo; Lee, Kyung Jin
Abstract: In this study, electrospun carbon nanofibers hybridized with silicon oxide (SiOx ) are prepared by using a syringeless electrospinning system of polyacrylonitrile (PAN) solution containing tetraethylorthosilicate (TEOS) via a sequential pyrolysis process. The syringeless electrospinning system provides a large number of composite nanofibers in a short time, and the obtained composite nanofibers exhibit uniform diameter and morphology. The composite nanofiber is converted into a carbon nanofiber containing SiOx via a simple pyrolysis. The obtained SiOx ‐carbon nanofiber mat exhibits higher charge/discharge capacity than a general carbon nanofiber, and it provides more stable retention than single crystalline silicon materials. Thus, the mass‐production of a SiOx ‐carbon nanofiber from syringeless electrospinning is a promising method to produce anodic materials for Li‐ion batteries. Abstract : A silicon oxide (SiOx )‐carbon nanofiber for anode material of a lithium‐ion battery is prepared via a syringeless electrospinning system and simple pyrolysis. The anode material with the SiOx ‐carbon nanofiber exhibits higher charging/discharging capacity when compared to that of carbon material and better retention capacity when compared with that of silicon materials.